2021
DOI: 10.1097/aud.0000000000001171
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Features and Cochlear Implantation Outcomes in Patients With PathogenicMYO15AVariants: a Multicenter Observational Study

Abstract: Objectives: Recessive variants in the MYO15A gene constitute an important cause of sensorineural hearing impairment (SNHI). However, the clinical features of MYO15A-related SNHI have not been systemically investigated. This study aimed to delineate the hearing features and outcomes in patients with pathogenic MYO15A variants.Design: This study recruited 40 patients with biallelic MYO15A variants from 31 unrelated families. The patients were grouped based on the presence of N-terminal domain variants (N variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Chen et al used multivariate generalized estimating equations analyses on 707 audiological records of 227 patients and concluded that hearing levels in patients with GJB2 mutations could be estimated using the following formula: predicted hearing level in dBHL = 3.78 + 0.96 x baseline hearing level in dBHL + 0.55 x duration of follow-up in year [ 9 ]. For patients with MYO15A mutations, an average progression rate for non-profound SNHI was 6.3 ± 4.8 dBHL per year [ 10 ]. In contrast, there is a paucity of studies that delineate the prognosis of hearing-impaired patients with negative genetic results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al used multivariate generalized estimating equations analyses on 707 audiological records of 227 patients and concluded that hearing levels in patients with GJB2 mutations could be estimated using the following formula: predicted hearing level in dBHL = 3.78 + 0.96 x baseline hearing level in dBHL + 0.55 x duration of follow-up in year [ 9 ]. For patients with MYO15A mutations, an average progression rate for non-profound SNHI was 6.3 ± 4.8 dBHL per year [ 10 ]. In contrast, there is a paucity of studies that delineate the prognosis of hearing-impaired patients with negative genetic results.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 200 genes have been implicated in HHI ( , last accessed on 19 February 2023). Because of its impact on speech/language development and cognitive functions [ 6 , 7 ], it is crucial to intervene in HHI early in life, and genetic testing assists in its prognostication and selection of management [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diagnosis plays a critical role in enabling clinicians to make informed decisions about electrode selection for cochlear implantation. Preservation of low and mid-frequency hearing has been observed in the early stages of certain genetic hearing impairments, such as pathogenic variants in the genes MYO15A [35,36], CDH23 [37], or TMPRSS3 [38]. How- ever, a significant proportion of this residual hearing tends to gradually deteriorate over time [35][36][37][38].…”
Section: Selecting CI Devices/electrodes Tailored To Patients With Sp...mentioning
confidence: 99%
“…Preservation of low and mid-frequency hearing has been observed in the early stages of certain genetic hearing impairments, such as pathogenic variants in the genes MYO15A [35,36], CDH23 [37], or TMPRSS3 [38]. How- ever, a significant proportion of this residual hearing tends to gradually deteriorate over time [35][36][37][38]. Therefore, for individuals with MYO15A, CDH23, or TMPRSS3 variants seeking cochlear implantation, electrode selection must consider both the preservation of residual hearing and the progression of SNHI, with a thin electrode of sufficient length being the preferred choice.…”
Section: Selecting CI Devices/electrodes Tailored To Patients With Sp...mentioning
confidence: 99%